Ligand-free rutile and anatase TiO2 nanocrystals as electron extraction layers for high performance inverted polymer solar cells. Issue 33 (5th April 2017) - Zhu, Lijie; Lu, Qipeng; Lv, Longfeng; Wang, Yue; Hu, Yufeng; Deng, Zhenbo; Lou, Zhidong; Hou, Yanbing; Teng, Feng
Abstract : Ligand-free rutile and anatase TiO2 nanocrystals were synthesized via a hydrolytic sol–gel method. The improved power conversion efficiency was achieved by using anatase TiO2 nanocrystals as electron extraction layer in the organic solar cells. Abstract : Ligand-free rutile and anatase TiO2 nanocrystals have been synthesized through a hydrolytic sol–gel reaction. The morphology, crystal structure, elemental composition and band structure of the obtained nanocrystals are characterized by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy and UV-visible absorption spectroscopy. These two kinds of nanocrystals could serve as electron extraction layers for improving the performance in inverted polymer solar cells. Compared with the device fabricated by using amorphous TiO2 (6.11%) and rutile TiO2 (6.93%), the device based on anatase TiO2 shows a significant enhancement in power conversion efficiency (7.85%). Meanwhile, the ideal current–voltage model for a single heterojunction solar cell is applied to clarify the junction property of the cell. The model demonstrates that the device based on anatase TiO2 has effective electron extraction and hole-blocking properties.